2017
DOI: 10.29252/nirp.jpcp.5.4.243
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the Roles of Hardiness and Hopelessness in Relation to Suicidal Ideation Among Malaysian Undergraduate Students

Abstract: Objective: Committing suicide is a growing issue across the globe, and it is essential to know the insights of the etiology of suicide. Therefore, we conducted this study to clarify the roles of hardiness and hopelessness in relation to suicidal ideation.Methods: This was a cross-sectional study. Study participants consisted of 500 (230 males and 270 females) Malaysian undergraduate students from two public universities during the fall semester 2014. All the respondents completed the Personal Views Survey, Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Studies have shown that individuals with high levels of hardiness are more likely to employ effective coping strategies to deal with problems, compared with those with low levels of hardiness . Previous studies have found hardiness to be a moderator in the links between problem‐solving skills and hopelessness with suicidal ideation for Malaysian undergraduate students who experience suicidal ideation. The purpose of this study is to explore the moderating role of hardiness in the link between perceived stress and hope among women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that individuals with high levels of hardiness are more likely to employ effective coping strategies to deal with problems, compared with those with low levels of hardiness . Previous studies have found hardiness to be a moderator in the links between problem‐solving skills and hopelessness with suicidal ideation for Malaysian undergraduate students who experience suicidal ideation. The purpose of this study is to explore the moderating role of hardiness in the link between perceived stress and hope among women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The BHS-Malay was validated amongst the Malaysian population and reported good psychometric properties with internal consistency reliability estimates that ranged from 0.71 to 0.91 ( 33 ). Convergent validity, construct reliability and Cronbach’s alpha for the BHS-Malay was found to be 0.60, 0.75 and 0.74, respectively, when tested on 500 Malaysian undergraduates ( 34 ).…”
Section: Methodsmentioning
confidence: 96%
“…Bartone and Bowles (2020) reported that stress and physical symptoms had a significant negative association with hardiness, supported by another study. The correlation between psychological hardiness and mental health is statistically significant; furthermore, studies show that psychological hardiness can reduce the negative symptoms associated with stress and improve mental health in general (Abdollahi, et al, 2017).…”
Section: Introductionmentioning
confidence: 94%